Heparin-Binding Protein Measurement Improves the Prediction of Severe Infection With Organ Dysfunction in the Emergency Department. Issue 11 (November 2015) - Linder, Adam; Arnold, Ryan; Boyd, John H.; Zindovic, Marko; Zindovic, Igor; Lange, Anna; Paulsson, Magnus; Nyberg, Patrik; Russell, James A.; Pritchard, David; Christensson, Bertil; Åkesson, Per
Abstract : Objectives: Early identification of patients with infection and at risk of developing severe disease with organ dysfunction remains a difficult challenge. We aimed to evaluate and validate the heparin-binding protein, a neutrophil-derived mediator of vascular leakage, as a prognostic biomarker for risk of progression to severe sepsis with circulatory failure in a multicenter setting. Design: A prospective international multicenter cohort study. Setting: Seven different emergency departments in Sweden, Canada, and the United States. Patients: Adult patients with a suspected infection and at least one of three clinical systemic inflammatory response syndrome criteria (excluding leukocyte count). Intervention: None. Measurements and Main Results: Plasma levels of heparin-binding protein, procalcitonin, C-reactive protein, lactate, and leukocyte count were determined at admission and 12–24 hours after admission in 759 emergency department patients with suspected infection. Patients were defined depending on the presence of infection and organ dysfunction. Plasma samples from 104 emergency department patients with suspected sepsis collected at an independent center were used to validate the results. Of the 674 patients diagnosed with an infection, 487 did not have organ dysfunction at enrollment. Of these 487 patients, 141 (29%) developed organ dysfunction within the 72-hour study period; 78.0% of the latter patients had an elevated plasma heparin-binding protein level (> 30 ng/mL) prior to development of organ dysfunction (median, 10.5 hr). Compared with other biomarkers, heparin-binding protein was the best predictor of progression to organ dysfunction (area under the receiver operating characteristic curve = 0.80). The performance of heparin-binding protein was confirmed in the validation cohort. Conclusion: In patients presenting at the emergency department, heparin-binding protein is an early indicator of infection-related organ dysfunction and a strong predictor of disease progression to severe sepsis within 72 hours. Abstract : Supplemental Digital Content is available in the text.